Enacted Agency in a Cross-Border, Online Biliteracy Curriculum Making: Creativity and bilingual digital storytelling - Zhang, Zheng; Li, Wanjing (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2020)
This research investigated potentials of bilingual digital story making to engage the creativity of 13 Canadian and Chinese biliteracy learners aged 11–15. Findings in this paper draw on six focal participants and their digital story creation. Informed by asset-oriented multiliteracies, new media literacies, and new materialism, this research adopted a netnography methodology to explore the communal and sociomaterial practices embedded in the intra-actions of human, matter, and virtual spaces of Seesaw and Skype. Drawing on data from six focal students, findings relate how intra-actions among researchers, teachers, students, matters, and spaces shaped participants’ creative acts. This research adds to the knowledge of developing and applying material-informed pedagogies which attend to the enacted agency among teachers, students, materials, and spaces.